2002
DOI: 10.5194/aab-45-287-2002
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of shortening and strength of eggshell to some egg quality indicators and egg production in hens of different initial laying lines*

Abstract: Abstract. The mean values of shortening force at fracture of egg found out during the five-month observation period ranged between 0.17 and 0.19 mm in 231 hens of seven initial laying lines and strength of eggshell ranged from 29.05 N to 36.46 N. The mean values of shortening force at fracture decreased with age of hens from 0.18–0.22 mm at 28 wk of age to 0.12–0.15 mm at 46 wk of age. Similarly, strength of eggshell decreased from 31.35–37.68 N to 27.91–34.50 N in same time period. Index of shape, ratio of eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
0
13
1
1
Order By: Relevance
“…With advancing quail age, production decreases with an associated increase in egg weight, and shell composition and thickness also change (MÁCHAL; SIMEONOVOVÁ, 2002). The increase in egg weight ratios can be up to 20%; however, there is no proportional increase in the weight of the shell because the calcium present in the shell is distributed over a larger surface.…”
Section: Introductionmentioning
confidence: 99%
“…With advancing quail age, production decreases with an associated increase in egg weight, and shell composition and thickness also change (MÁCHAL; SIMEONOVOVÁ, 2002). The increase in egg weight ratios can be up to 20%; however, there is no proportional increase in the weight of the shell because the calcium present in the shell is distributed over a larger surface.…”
Section: Introductionmentioning
confidence: 99%
“…A good-quality day-old chick is hence a crucial hinge between the hatchery and farm. Pre-incubation factors such as pre-storage incubation, length of egg storage and age of breeders, as well as incubation conditions, affect day-old chick quality and subsequent bird performance (MACHAL andSIMEONOVOVA 2002, PETEK andDIKMEN 2006). Moreover, it has been reported that good hatchability does not necessarily positively correlate with a high percentage of good-quality chicks and that maximal hatchability is not always linked to the highest post hatch quality and growth of the chick (DECUYPERE and BRUGGEMAN 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The rupture force of hen eggs depends on various factors such as breeding conditions , the breed of hen (Máchal, 2002), diet , egg shape (Havlíček et al, 2008;Nedomová et al, 2009), microstructure (Severa et al, 2010a;Severa et al, 2010b), temperature (Voisey & Hamilton, 1976) and other parameters. This force also depends on loading rate.…”
Section: Introductionmentioning
confidence: 99%